Analysis of Curriculum and Resource Management in Mandiri Bakti Playgroup (KB) - Zaahirah, Zaahirah; Fitriana, Aulia Dinda; Jais, Unzila; Harefa, Putri Enjelina; Laing, Jaat; Virmeisna, Alysa (Proceeding of Annual International Conference on Islamic Education and Language (AICIEL), 2025)
Early Childhood Education (ECE) is paramount for developing quality human resources for the future. KB Mandiri Bakti is an ECE institution responsible for implementing effective curriculum management to ensure learning is enjoyable, contextual, and aligned with child development. The purpose of this study was to examine how KB Mandiri Bakti manages its resources and curriculum. This research adopted a qualitative descriptive approach, with data collected through participant observation, documentation, and in-depth interviews. The analysis aimed to understand the processes of curriculum planning, implementation, and evaluation within the institution. The findings indicate that curriculum management at KB Mandiri Bakti is functioning adequately. However, several constraints exist, notably in planning a curriculum truly based on individual child needs, facility shortages, and limited teacher competency development. Parental support and strong collaboration are highlighted as crucial factors for successful synchronization. Overall, curriculum management at KB Mandiri Bakti relies heavily on the cooperation among teachers, the principal, infrastructure management, and parental participation.